Kajian Hukum Pidana Penyalahgunaan Dana Gereja: Studi Kasus Kupang Timur - Juane Priskila; Deddy R. Ch. Manafe; Ngongo Dede (Law Faculty, Nusa Cendana University, 2026)
Misuse of funds occurred in two churches with a difference in funds that could not be accounted for by the previous treasurer, and the takeover of the management of church construction funds by active military members. Based on these problems, this study aims to determine and understand the criminal acts that occur in the management of church funds, as well as the form of criminal responsibility carried out in the East Kupang Classis and the Imatha Yonif 743/PSY Naibonat Church. The type of research used is empirical legal research, through an approach that emphasizes legal analysis seen from social reality. This study not only examines the applicable written legal norms, but also examines the application of the law in society, especially in the misuse of church funds. Data were obtained directly from the research location through interview techniques with sources from the East Kupang Classis Congregation and the Imatha Yonif 743/PSY Naibonat Congregation. In addition, data were also obtained from reading several literatures that were in accordance with the problem, then analyzed descriptively qualitatively. The results of the study show that the settlement of the case against the two churches was carried out internally by providing compensation in the form of replacement money by the parties involved and the dismissal of active military members from their positions as deputy chairmen of the congregation council. Therefore, a firm legal strategy and internal church policy are needed to strengthen the integrity and transparency in the financial management of religious institutions.